The evolution of feminist literature in the Arab world - Khatib, Gaida (Humaniora. Czasopismo Internetowe, 2019)
In this article, we try to discuss the concept of the term “feminine literature” and the problems related to that in both Western and Arab worlds, with a historical overview of the evolution of Arab feminist literature from the pre-Islamic era to the present day. Besides that, we will relate to the difference between the writing of man and woman, as woman was distinguished by her own style as well as the issues she raises. However, despite the efforts, there has been a clear marginalization of woman’s writing, and there was no clear definition of the term.